Pembinaan Masyarakat Berbasis Kearifan Lokal dalam Rangka Penetapan Hari Jadi Desa Bojong - Dede Nurul Qomariah; Imas Masitoh; Gilang Anjar Prasetya; Acep Wildan Mubarok; Pajrin Nurlina; Alfiyatun Alfiyatun; Mintarsih Mintarsih (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
The Bojong Village is one of the villages in Parigi Sub-district, Pangandaran Regency, which has a variety of promising local potentials. Currently, Bojong Village is one of the supporters of the natural tourism sector that supports the world of local-based tourism. However, from a socio-cultural point of view, the community in Bojong Village does not know the history of the village's development in the past, making it difficult for the community to determine the village's anniversary. So that social cohesion is minimally built and it is feared that it will trigger division. The service method carried out in this service was carried out through the participatory action research (PAR) method. The results of the service concluded that the determination of the village anniversary was successfully carried out through several stages, namely: cross-history search, symposium, and panel discussion between figures. Therefore, community development based on local wisdom in the context of determining the anniversary of Bojong Village can be said to be successfully carried out. The results of the service led to the establishment of the anniversary of Bojong Village, a memorandum of understanding of the anniversary of Bojong Village signed by the leaders, and a small book of resume of the history of Bojong Village. The implication of this service is the existence of a village regulation related to the determination of the anniversary of Bojong Village.